2004
DOI: 10.2528/pier04031301
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Coupling to Circulant Symmetric Multi-Conductor Microstrip Line

Abstract: Abstract-In this paper a method is introduced and applied to calculate the effects of an external field on a circular symmetric microstrip transmission line. The primary/secondary field idea is used for this purpose. The primary field is determined analytically for the cases of normal TM z and TE z incidence. The secondary field is determined using multi-conductor transmission line theory. The method is applied to a special structure and some useful results are obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Applications of the FDTD method to the full-wave solution of Maxwell's equations have shown that accuracy and stability of the solution can be achieved if the electric and magnetic field solution points are chosen to alternate in space and be separated by one-half the position discretization, e.g., ∆x/2, and to also be interlaced in time and separated by ∆t/2 [13][14][15]. To incorporate these constraints into the FDTD solution of the transmission-line equations, we divided each line into N x sections of length ∆x, as shown in Fig.…”
Section: The Fdtd Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Applications of the FDTD method to the full-wave solution of Maxwell's equations have shown that accuracy and stability of the solution can be achieved if the electric and magnetic field solution points are chosen to alternate in space and be separated by one-half the position discretization, e.g., ∆x/2, and to also be interlaced in time and separated by ∆t/2 [13][14][15]. To incorporate these constraints into the FDTD solution of the transmission-line equations, we divided each line into N x sections of length ∆x, as shown in Fig.…”
Section: The Fdtd Formulationmentioning
confidence: 99%
“…First the voltages along the line were solved for a fixed time using (20) then the currents were determined using (21). The solution starts with an initially relaxed line having zero voltage and current [13,14].…”
Section: The Fdtd Formulationmentioning
confidence: 99%
“…If the cable network is complex and its overall structure is electrically large, it is very difficult to handle its EM coupling problems using the full-wave method. One efficient way is that the external fields can be linked with MTL model by introducing a set of distributed voltage and current sources, as proposed in [17] and [18], respectively. In the implementation of the field-line coupling model, the coupling process of electric and magnetic fields can be simply transformed into the coupling of currents and voltages through the transfer impedance between the internal and external shielded cables.…”
Section: Field-line Em Coupling Modelsmentioning
confidence: 99%